Rose, a Potential Nutraceutical: An Assessment of the Total Phenolic Content and Antioxidant Activity - Vun, Vui Fui; Poh, Siong Chin; Yim, Hip Seng (Journal of Pharmacy and Nutrition Sciences, 2013)
Rosa hybrida L. was reported to contain high total phenolic content and antioxidant activity. The scarce information on antioxidant properties of Malaysian cultivated R. hybrid L. had lead to the present study, which aimed to determine the effect of different solvent extraction on the total phenolic content and antioxidant activity of roses of different colours. All the 23 R. hybrida L. cultivars’ petals extracted with 70% ethanol had significantly higher 2,2-diphenyl-1-picryl-hydrazyl (DPPH) radical scavenging activity compared to the water extraction. The five cultivars (03, 203, 205, 402 and M203) that comprise the highest DPPH scavenging activity were subjected to various antioxidant assays. Cultivar M203 showed highest total phenolic content (TPC) at all concentration. Cultivar M203 and 402 gave higher DPPH radical scavenging ability (EC50=107.08 µg/ml) and 2,2-azino-bis(3-ethylbenzo-thiazoline-6-sulfonic acid) (ABTS) radical cation scavenging ability (EC50=258.13 µg/ml). In ferric reducing antioxidant power assay, cultivar M203 has the highest trolox equivalent value at 200, 300 and 500 µg/ml concentrations while in b-carotene bleaching assay, cultivars 03, 205, and M203 (at the concentration of 500 µg/ml) showed higher antioxidant activity than synthetic antioxidant (BHA). Strong positive correlations were found between TPC and antioxidant activities, hence, suggesting that the high antioxidant activity of selected R. hybrida L. petals might be mainly contributed by the phenolic compounds. In general, cultivar M203 showed the best antioxidant activity with nutraceutical potential.